Identification of methyltransferase and demethylase genes and their expression profiling under biotic and abiotic stress in pigeon pea (Cajanus cajan [L.] Millspaugh) - Kumari, Priyanka; Bhattacharjee, Sougata; Venkat Raman, K.; Tilgam, Jyotsana; Paul, Krishnayan; Senthil, Kameshwaran; Baaniya, Mahi; Rama Prashat, G.; Sreevathsa, Rohini; Pattanayak, Debasis (Frontiers in Plant Science, 2025)
The methylation- demethylation dynamics of RNA plays major roles in different biological functions, including stress responses, in plants. m6A methylation in RNA is orchestrated by a coordinated function of methyl transferases (writers) and demethylases (Erasers). Genome-wide analysis of genes involved in methylation and demethylation was performed in pigeon pea. Blast search, using Arabidopsis gene sequences, resulted in the identification of two methylation genes (CcMTA70, CcMTB70), two genes encoding adaptor proteins for methylation (CcFIPA and CcFIPB) and 10 demethylase (ALKBH) genes (CcALKBH1A, CcALKBH1B, CcALKBH1C, CcALKBH2, CcALKBH8, CcALKBH8A, CcALKBH8B, CcALKBH9, CcALKBH10A and CcALKBH10B) in the pigeon pea genome. The identified genes were analyzed through phylogenetic relationship, chromosomal position, gene structure, conserved motif, domain and subcellular location prediction etc. These structural analyses resulted in categorization of MTs and FIPs into one group, i.e., CcMTA/B and CcFIPA/B, respectively; and ALKBHs into four groups, viz. CcALKBH1/2, CcALKBH8, CcALKBH9 and CcALKBH10. Relative expression analysis of the identified genes in various tissues at different developmental stages revealed the highest level of expression in leaf and the least in root. CcMTs and CcFIPs had similar patterns of expression, and CcALKBH10B demonstrated the highest and CcALKBH2 the lowest level of expression in all the tissues analyzed. CcALKBH8 showed the highest induction in expression upon exposure to heat stress, and CcALKBH10B demonstrated the highest level of induction in expression during drought, salt and biotic (Helicoverpa armigera infestation) stresses. The present study would pave the way for detailed molecular characterization of m6A methylation in pigeon pea and its involvement in stress regulation.